Nesidioblastosis and Insulinoma: A Rare Coexistence and a Therapeutic Challenge - Dardano, Angela; Daniele, Giuseppe; Lupi, Roberto; Napoli, Niccolò; Campani, Daniela; Boggi, Ugo; Del Prato, Stefano; Miccoli, Roberto (Frontiers in Endocrinology, 2020)
Background: Nesidioblastosis and insulinoma are disorders of the endocrine pancreas causing endogenous hyperinsulinemic hypoglycemia. Their coexistence is very unusual and treatment represents a still unresolved dilemma. Case Description: The patient was a 43-year-old Caucasian woman, with a 2-year history of repeated severe hypoglycemic events. The diagnostic work-up was strongly suggestive of insulinoma and the patient was submitted to surgical treatment carried out laparoscopically under robotic assistance. However, surgical exploration and intraoperative ultrasonography failed to detect a pancreatic tumor. Resection was therefore carried out based on the results of selective intra-arterial calcium stimulation test, following a step-up approach, eventually leading to a pancreatoduodenectomy at the splenic artery. The histopathology examination and the immunohistochemical staining were consistent with adult-onset nesidioblastosis. After surgery, the patient continued to experience hypoglycemia with futile response to medical treatments (octreotide, calcium antagonists, diazoxide, and prednisone). Following multidisciplinary evaluation and critical review of a repeat abdominal computed tomography scan, a small nodular lesion was identified in the tail of the pancreas. The nodule was enucleated laparoscopically and the pathological examination revealed an insulinoma. In spite of the insulinoma resection, glycemic values were only partially restored, with residual nocturnal hypoglycemia. Administration of uncooked cornstarch (1.25 g/kg body weight) at bedtime was associated with significant improvement of interstitial glucose levels (p < 0.0001) and reduction of nocturnal hypoglycemia episodes (p = 0.0002). Conclusions: This report describes a rare coexistence of adult-onset nesidioblastosis and insulinoma, suggesting the existence of a wide and continuous spectrum of proliferative β-cell changes. Moreover, we propose that uncooked cornstarch may offer an additional approach to alleviate the hypoglycemic episodes when surgery is impracticable/unaccepted.